The Digital Transformation of the Classroom – the What, How, and Why in Austrian Secondary Colleges of Agriculture and Forestry - Erika Quendler (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 12-14 September 2019, 2019)
Throughout the education system, more and more classrooms are using digital technology. Although the idea of a digital or smart classroom has been around for years, electronic technology such as tablets, laptops, smartphones, and e-readers enable learning anytime and anywhere. They support all pupils in more easily reaching their full potential in college and further careers. This paper focuses on the evaluation of the digital transformation at secondary colleges for agriculture and forestry. Aiming to help colleges in their understanding of the digital transformation process, this paper discusses the what, how, and why of this transformation. Data from an online survey of 1,963 pupils has been analysed as a backdrop to the exploratory research in this paper. While digital transformation does not have a finish line, there are certain steps that drive a sustainable and smart transformation. There may even be benefit in having a framework for the digital transformation of colleges. Digital transformation in Austrian secondary colleges of agriculture and forestry should enable constant innovation and enhance teaching and learning. This notwithstanding, it must be supported by a combination of vision and leadership, process and methodology, culture and research, as well as by the technology itself
Keywords: I20; I21; I29; Q19; 330; digital transformation; key design principles; secondary colleges for agriculture and forestry; Austria